India emerging: New financial architecture. Issue 3 (September 2016) - Basu, Sankarshan
Abstract: The global financial crisis of 2007–2008 highlighted the need to re-evaluate several well established tenets in the world of finance. Questions have been raised the world over about the existing paradigm, leading to an acceptance that new financial architecture needed to be evolved and that new models need to emerge, keeping in mind the multiplicity of socio-economic realities that exist round the globe. In this context, the imperative for a new financial architecture in India is quite evident, and the ensuing panel discussion throws up some India-specific issues that need to be explored by the various stakeholders involved in this attempt.